Structural and Oxidative Properties of Manganese Incorporated Mesostructure Silica for Methane Oxidation - Rihem Dardouri; Anis Gannouni; Mongia Saïd Zina (Advances in Materials Science and Engineering)
Manganese catalysts containing templated mesostructured porous silica were prepared using different methods of preparation, namely, the direct hydrothermal (DHT), solid-state ion exchange (SSI), template ion exchange (TIE), and impregnation (Imp) methods. The physical-chemical properties of materials were characterized by X-ray diffraction (XRD), N2 adsorption-desorption, FT-IR, TEM, EDX, UV-Vis, EPR, and H2 TPR techniques. The results of this study indicate that the obtained catalysts retained their hexagonal mesopore structure after introducing Mn into MCM-41. On the contrary, the crystalline phase of manganese oxide was stabilized on the external surface and inside the mesoporosity of the MCM-41 and seems to be dependent on the synthesis method used. Catalytic performances of synthesized materials were then investigated in methane oxidation at atmospheric pressure. The results showed that the metal loading and catalysts synthesis procedure influence the catalytic performance of the obtained materials. Moreover, the activity of the catalyst depends on the crystalline phase and particularly on the environment of the active phase.